Antibacterial activity of phenolic compounds from seed of Persea americana Mill. "Hass avocado" front Escherichia coli - Romaní, Lía (2018)
In the present study was determined the antibacterial activity of the phenolic compounds of the ethyl acetate fraction isolated from Persea americana Mill. seed "Hass avocado". The avocados were harvested in the province of Huanta and the seeds were subjected to an ethanolic extraction process, degassed with petroleum ether and finally extracted with ethyl acetate. The phenolic compounds were isolated by thin layer chromatography and identified by ultraviolet spectrophotometry. The Kirby Bauer disc diffusion method was used using the strains of Escherichia coli ATCC 35218; Which were tested at concentrations of 1, 2,5, 5, 10 and 15%; ciprofloxacin 30 μg was used as the control. The ethyl acetate fraction showed phenolic compounds and flavonoids, showed an antibacterial activity of 81,5% inhibition at 10%; minimum inhibitory concentration of 0,625 mg/mL and minimum bactericidal concentration of 1,250 mg/mL with statistically significant inhibition halos p < 0,05. Was concluded that the ethyl acetate fraction from the Persea americana Mill. seed has phenolic compounds with antibacterial activity against Escherichia coli ATCC 35218.